The Value of Attribution to Strengthen Self-Efficacy and Self-Regulation of Islamic Boarding School Students - Kibtiyah, Asriana; Arini, Aida (MANAZHIM, 2024)
Today, the education system in Islamic boarding schools has been transformed compared to when it was first established. Previously, students only studied religious sciences and did not study general sciences. These changes encourage management in the Islamic boarding school environment to be somewhat different so that it impacts the comfort of students which in turn will determine the students' academic achievement. The success of an educational process is characterized by the achievement of students in the academic field and the ability of students to regulate themselves well. Moreover, Islamic boarding schools' education and parenting systems have this achievement target. The problem is what needs to be investigated better. This study aims to test Attribution variables that strengthen Self-Efficacy and Self-Regulation. These three variables will affect academic achievement and other factors behind it. The study sample comprised 108 Class IX junior high school (SMP) students. The results showed that the attribution variable had an effect on increasing self-efficacy, and the variable on self-efficacy had an impact on improving self-regulation.